Development of digital comics as learning media on bacteria - Yulilina Retno Dewahrani; Shania Putri Apriani; Tri Handayani Kurniati (Biosfer: Jurnal Pendidikan Biologi, 2023)
71% of students of class X IPA SMAN 36 Jakarta,Indonesia have difficulties in studying Biology subjects and 47.2% of students have difficulties in learning topics about bacteria. The research aims to develop digital comics as a medium for learning Biology on bacteria. The research method refers to the research and development model of Borg and Gall (2003). Data was collected with questionnaires to analyze student needs and interviews with Biology teachers in class X IPA. Digital comic was made by Autodesk-SketchBook design application. Product validation was carried out by media and material experts. The product trial consisted of a small group of 12 students, a large group consisting of 46 students, and a biology teacher. The average validation test results obtained a score of 91.69% with a very valid interpretation. The product effectiveness test uses a pre-test and post-test instrument consisting of 30 questions. Analysis of the data obtained an average pre-test score of 70.33 and post-test score was 81.08 with a standard error of 1,432-2.094. The results of the t-test showed a significant value of 0.00 < = 0.05 and the value of t-count < t-table which was -5.847 <2.715, which means the difference is statistically significant or significant at a probability of 0.05. Thus, it can be concluded that there is an effect of using digital comic learning media on bacterial material to improve learning outcomes.